COMMERCIAL KIDNEY ORGAN TRANSPLANTATION FROM THE PERSPECTIVE OF POSITIVE LAW AND ISLAMIC LAW - Aidil, Muhammad (Inspiring Law Journal, 2025)
In the medical world, commercial practices in kidney organ transplantation often occur, with economic motives as the background. This practice is prohibited by positive law, both at the national and international levels, as well as by Islamic law. There are differences of opinion between positive law and Islamic law in regulating organ transplantation. Therefore, the author will discuss the legal regulation of kidney organ transplantation from the perspective of positive law and Islamic law. This study aims to analyze the legal regulation of kidney organ transplantation from the perspective of positive law and Islamic law, as well as the application of sanctions for perpetrators of illegal transplantation and preventive measures that can be taken. The method used is normative juridical legal research with a legislative and conceptual approach. The data sources used include primary, secondary, and tertiary data. The results of the study indicate that kidney transplantation must be carried out voluntarily, without coercion or compensation. The practice of organ trafficking is prohibited by positive law and Islamic law. However, there are differences between positive law and the views of the four schools of thought; positive law allows healthy donors, while the schools of thought prohibit transplantation in healthy or dying conditions. This study recommends that the government prevent organ trafficking by improving the economic welfare of the community.